Lepiota cremea, a novel species of Lepiota sect. Lepiota (Agaricaceae s.l., Agaricales) from Turkey - Kaygusuz, Oğuzhan (Phytotaxa, 2022)
A new species of Lepiota from Turkey, Lepiota cremea sp. nov., is proposed based on morphological characters and phylogenetic analyses of the nuclear rDNA internal transcribed spacer (ITS1-5.8S-ITS2 = ITS) region. The morphological features together with molecular data confirmed both the novelty of this species and its infrageneric placement within Lepiota sect. Lepiota. Lepiota cremea, so far only found in Pinus nigra subsp. pallasiana forest, is characterized by the pale beige basidiomata, subcylindrical to fusiform basidiospores, long pileus covering elements with often nodulose or horn-like bumps. A comprehensive description, illustrations and comparisons with morphologically similar and related taxa are provided.